SPORTS AND INTERNATIONAL COOPERATION IN UZBEKISTAN DURING THE SOVIET PERIOD (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article analyzes the formation and development of the physical education and sports system during the Soviet era. Special attention is given to reforms implemented in Uzbekistan in the field of sports, competitions organized among students and youth, women’s participation in sports, and the expansion of sports infrastructure. Based on archival sources and scientific literature, the study demonstrates the increasing socio-educational importance of sports in society and the growing international reputation of Soviet athletes.